A History of Japan's Government-Business Relationship The Passenger Car Industry - Genther, Phyllis A. (Michigan Papers in Japanese Studies, 2020)
Despite the economic and political importance of the U.S.-Japan relationship and the extensive attention paid to automotive trade, few American scholars or policy makers are familiar with the history of Japanese government-business relations, either generally or for specific industries such as passenger cars. This book hopefully helps in a small way to fill that gap in our knowledge and, thus, to help strengthen the foundation from which we make public policy decisions about bilateral trade. [ix]